Um estudo sobre a formação continuada e sua contribuição para o desenvolvimento profissional docente e a mobilização da práxis de professores que ensinam matemática - Leão, Alex Sandro Gomes (2021)
This research was developed between the years 2017 and 2018 where different continuing education courses were analyzed in the city of Itaqui / RS, with the participation of teachers of basic education and graduation students in Mathematics Degree from Universidade Federal do Pampa - Unipampa - Campus Itaqui. The aim of the study was to investigate the elements present in different continuing education activities developed in the city of Itaqui-RS, and how they have contributed to the professional development and the mobilization of the teaching praxis of teachers who teach mathematics. Characterized as a qualitative Case Study, the study provided the opportunity to write three scientific manuscripts. The first one addresses “The role of PNAIC as continuing education and its possible contribution to the teaching professional development”, the second manuscript analyzes “The process of continuing education in a group of Mathematics teachers: perceptions, trajectory and praxis” and the third investigates “Academic-Professional Training and Teacher Professional Development: A common space?”. It was identified that the training in this area is punctual, and in some cases of interest more to the former than to the participating teachers, being removed from the reality of the school. However, there are contributions to the professional development of teachers and to the mobilization of the praxis of participating teachers. The analyzed results allow the construction of the following statements: The formations need to be planned in conjunction with participating teachers; They must take their needs into consideration; The school needs to take responsibility in the formation of its teachers; They need to invest in training reflective teachers and; Roda de Conversa is a training strategy with the potential to bring together primary school teachers, researchers and students in professional induction in the same environment. Thus, for new continuous training to occur, a partnership is proposed so that it is developed in an integrated space between the University and the School, valuing the teaching profession, in the knowledge of the most experienced teachers, and in the theoretical knowledge of students in Estágio Curricular Supervisionado em Ensino de Matemática, Pibid, Residência Pedagógica and the researcher teacher. Considering the reality of Brazilian schools, this training space must be built within the school, with days and times for it to be implemented. In the same way that, for this practice to occur, it is necessary to reformulate the components of Estágio Curricular Supervisionado em Ensino de Matemática, where in addition to the required observations, and the effective teaching of classes, there must be a space for na dialogical interface between undergraduate students and teachers of basic education.